Pengaruh teknik sosiodrama untuk meningkatkan komunikasi interpersonal siswa melalui bimbingan kelompok di SMP negeri 13 Pekanbaru - Agustin, Ade Mahalia; Arlizon, Raja; Donal, Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to knowing the differences in interpersonal communication of students before anda after sociodrama thehnique was applied through group guidance and knowing the effect of sociodrama thechnique to improve student interpersonal communication through group guidance. The study was conducted in pekanbaru state SMP 13 towards 7 subjects with purposive sampling technique. One group pre-test post-test dmodel the data collectionn instrumen used was a personal communic measurement scale adapted from evi zuhara 2014. The results showed that there were differences in interpersonal communication before and after being given sociodrama technique with a significance value of 0,018 < 0,05 in addition, based on the spearman rank test, it is known that there is a signifivant effect between improve students personal communication significance 0,041< 0,05. The influence of sociodrama technique to improve student interpersonal communication is 60% ehole 40% effect by other factors that come from the student;s environtment. From the results obtained, it is recommended that educational institutions should continue to carry out activities that are able to improve students interpersonal communication in the teaching and learning proccess to encourage more perpersonal communication in the teaching and learning proccess to encourage more positive thoughts, perceptions, insight and student attitudes.Key Words: Sosiodrama, interpersonal communication, group guidance